2014
DOI: 10.1002/ejp.526
|View full text |Cite
|
Sign up to set email alerts
|

Out of sight, but not out of mind? Greater reported pain in patients who spontaneously look away during venepuncture

Abstract: Almost three quarters of patients spontaneously look away during venepuncture, but their pain ratings are almost twice that of the quarter of patients who look. It is unclear why this may be, but previous experimental studies indicate that observing the body when a noxious stimulus is applied can have an analgesic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Protective factors are strengths of the child or adult that reduce the severity of problems or promote healthy and adaptive functioning. For example, in 1 study, adults who self-selected to look at (ie, expose themselves to) the needle going into their arm reported less pain compared with those who chose to look away (ie, avoided) 89 (but also see Goodenough et al 43 ). Having a behavioral predisposition to face a fear-inducing stimulus could be a protective factor against developing a high level of needle fear; in fact, a key component of evidence-based treatments for phobias is exposure.…”
Section: Needle Fear and Phobiamentioning
confidence: 99%
“…Protective factors are strengths of the child or adult that reduce the severity of problems or promote healthy and adaptive functioning. For example, in 1 study, adults who self-selected to look at (ie, expose themselves to) the needle going into their arm reported less pain compared with those who chose to look away (ie, avoided) 89 (but also see Goodenough et al 43 ). Having a behavioral predisposition to face a fear-inducing stimulus could be a protective factor against developing a high level of needle fear; in fact, a key component of evidence-based treatments for phobias is exposure.…”
Section: Needle Fear and Phobiamentioning
confidence: 99%
“…In addition, 1 study was excluded as it presented data from the same sample as an included study, but did not examine any critical outcomes. 32 Altogether, 7 studies used a between-groups (parallel) design, and 1 study used a cross-over design. All studies provided data for 2 or more treatment arms.…”
Section: Resultsmentioning
confidence: 99%
“…One simple intervention used by some clinicians to reduce fear and pain involves advising individuals to look away from the needle during injection. 10 To our knowledge, there are no randomized trials that have determined the effectiveness of this intervention with respect to reducing fear or pain during vaccination. In four nonclinical and one clinical observational study performed to date, conflicting results were obtained for self-reported pain after asking healthy adults to either look at versus look away during a painful stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…In four nonclinical and one clinical observational study performed to date, conflicting results were obtained for self-reported pain after asking healthy adults to either look at versus look away during a painful stimulus. 10 , 13 16 Higher pain scores during looking have been explained as possibly due to increasing autonomic nervous system activity in the individual. 13 , 14 Conversely, lower pain scores during looking have been explained as possibly preventing an individual’s imagination from conjuring up a more traumatic experience than reality.…”
Section: Introductionmentioning
confidence: 99%